Perlindungan Hukum Peserta Arisan Online Akibat Tindakan Wanprestasi Penyedia “Arisan Online” Berdasarkan Buku III Kitab Undang-Undang Hukum Perdata - Kiki Rizki Ananda; Ananda, Rimba Supriatna (Bandung Conference Series: Law Studies, 2024)
The development of communication technology gave birth to various phenomena in society, one of which is the phenomenon of online arisan. Previously, arisan was often found in the midst of Indonesian society and was carried out conventionally by holding meetings between its members. Nowadays, arisan can be found online through various social media with various types and ways of implementation. In arisan, there is an engagement relationship between arisan members and the relevant arisan chairman or owner. In general, arisan is carried out only with an oral agreement between the members and the chairman. Online arisan activities are not free from various problems such as the negligence of the parties in carrying out their obligations. Therefore, this thesis will specifically discuss the case in verdict Number 2/Pdt.G.S/2021/PN Trt regarding protection due to default actions of online arisan providers and the application of Law by Judges in verdict Number: 2/Pdt/G.S/2021/PN Trt against compensation claimed by online arisan participants for default by online arisan providers based on Book III of the Civil Law. This research uses normative juridical research methods by using laws and regulations as primary legal materials and qualitative research types. The research specification is descriptive analytical to obtain a comprehensive description and analysis by describing the laws and regulations. The results of this study show that the form of legal protection given to online arisan participants is repressive legal protection in the form of rules related to online arisan formulated in the Civil Law. Repressive legal protection in the form of compensation. The profit fee agreed by the parties in the agreement was not fulfilled by the judge on the grounds of the principle of justice of the online arisan provider. In this case, the Judge's application of law is inconsistent in his considerations. On the other hand, the Judge's decision is made based on his authority as stipulated in the Judicial Power Act.